Penegakan Prinsip Keadilan Sosial dalam Redistribusi Tanah melalui Program Reforma Agraria: Telaah Yuridis dan Empiris - Bora, Yuyun; Fatifah Saini, Armida Putri; Moonti, Roy Marthen (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The high inequality of land ownership in Indonesia shows that the enforcement of social justice in the implementation of land redistribution has not been running optimally. The agrarian reform program which is expected to be a solution to overcome agrarian inequality is often hampered by structural, legal, and institutional problems. This study aims to examine legally and empirically how the principle of social justice is upheld in the practice of land redistribution through the agrarian reform program. The method used is qualitative research with a normative and empirical legal approach, through a literature study of regulations and academic literature as well as secondary data analysis from government reports, scientific journals, and field studies. The results of the study show that although there is a supporting legal framework, the implementation of land redistribution still faces obstacles such as weak transparency, lack of community participation, and ineffective supervision of the use of ex-HGU land. This study contributes to understanding the importance of integration between legal aspects and social justice in agrarian reform policies. In conclusion, the enforcement of the principle of social justice in agrarian reform requires more inclusive policies that favor marginalized groups, as well as further in-depth and interdisciplinary research to formulate strategies for implementing equitable and sustainable reforms.